Pacing interventions in non-responders to cardiac resynchronization therapy - Wijesuriya, Nadeev; Elliott, Mark K.; Mehta, Vishal; De Vere, Felicity; Strocchi, Marina; Behar, Jonathan M.; Niederer, Steven A.; Rinaldi, Christopher A. (Frontiers in Physiology, 2023)
Non-responders to Cardiac Resynchronization Therapy (CRT) represent a high-risk, and difficult to treat population of heart failure patients. Studies have shown that these patients have a lower quality of life and reduced life expectancy compared to those who respond to CRT. Whilst the first-line treatment for dyssynchronous heart failure is “conventional” biventricular epicardial CRT, a range of novel pacing interventions have emerged as potential alternatives. This has raised the question whether these new treatments may be useful as a second-line pacing intervention for treating non-responders, or indeed, whether some patients may benefit from these as a first-line option. In this review, we will examine the current evidence for four pacing interventions in the context of treatment of conventional CRT non-responders: CRT optimization; multisite left ventricular pacing; left ventricular endocardial pacing and conduction system pacing.